Analisis Faktor yang Mempengaruhi Penyerapan Tenaga Kerja pada Sektor Pariwisata di Provinsi Jawa Timur (2018-2023) - Khurun Estina Savira; Annis Nurfitriyana Nihayah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
East Java Province has great potential in the tourism sector, as reflected by the high number of tourist visits. However, its contribution to the regional economy remains low, posing challenges in labor absorption. This study aims to analyze the factors influencing labor absorption in the tourism sector of East Java Province during the 2018–2023 period using panel data sourced from the Central Bureau of Statistics (BPS). Based on specification tests, the Fixed Effect Model (FEM) was selected as the best model, and analysis was conducted using the Feasible Generalized Least Squares (FGLS) method. The results show that education, technology, regional minimum wage (UMK), and Gross Regional Domestic Product (GRDP) of tourism simultaneously have a significant effect on labor absorption. Partially, education, UMK, and tourism GRDP have a positive and significant effect, while technology has a negative and significant effect. The model explains 91.14% of the variation in labor absorption, with the remaining variation explained by other factors outside the model.